Effectiveness of pharmacological procedural sedation in children with cerebral palsy undergoing botulinum toxin injection: a systematic review and meta-analysis - Lazzaretto, Veronica; Barbi, Egidio; Carraro, Carolina; Sutera, Marco; Celsi, Fulvio; Peri, Francesca; Zupin, Luisa (Frontiers in Pediatrics, 2025)
Botulinum toxin injection (BTI) is a well-established therapeutic option for focal spasticity in children with cerebral palsy (CP). However, the procedure is associated with significant anxiety, pain, and discomfort, highlighting the importance of using sedation and distraction techniques. To date, no specific guideline exists for procedural sedation during BTI in children with CP. Therefore, we conducted a systematic review and meta-analysis to investigate the strategies for improving the experience of children with CP during BTI. Articles published up to July 2024 were identified through PubMed searches, and after screening, ten studies involving children aged 0–18 with CP were selected. Pain levels during BTI procedure was assessed using specific pain scales. Nitrous oxide was used as a sedation treatment in 7 studies, either alone (3 studies), combined with topical anaesthetic (3 studies), or alongside both topical anaesthetics and distraction techniques (2 studies). Its use reduced distress, with the greatest effect when combined with topical anaesthetic. These results suggest that the combination of pharmacological and non-pharmacological methods may be a reasonable approach. The most common limitations of the studies included were the absence of a clear definition of the degree of cognitive impairment, the lack of dedicated pain assessment scales, insufficient consideration of caregiver involvement, and of non-pharmacological techniques. Further research is needed to establish standardized guidelines for procedural sedation during BTI in children with CP, focusing on randomized controlled study designs, precise population definitions, the effectiveness of distraction techniques, caregiver involvement, and the use of dedicated pain assessment scales.